2016
DOI: 10.1126/sciadv.1501859
|View full text |Cite
|
Sign up to set email alerts
|

Claisen thermally rearranged (CTR) polymers

Abstract: Second generation of thermally rearranged polymers presents low temperatures for a complete rearrangement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 39 publications
(51 reference statements)
1
17
0
Order By: Relevance
“…The auxiliary liquid for the measurement was isooctane as a liquid with low density and very low solubility in studied polymers. FFV was calculated according to the method described elsewhere [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The auxiliary liquid for the measurement was isooctane as a liquid with low density and very low solubility in studied polymers. FFV was calculated according to the method described elsewhere [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Tena et al 42 have reported a novel low-temperature chemistry using a Claisen rearrangement reaction (CR) for the preparation of microporous polymers. The reaction was reported to occur at temperatures of ca 300 ∘ C (Scheme 10).…”
Section: Macromolecular Tr Chemistry Tr: Polybenzoxazolesmentioning
confidence: 99%
“…Tena et al . have reported a novel low‐temperature chemistry using a Claisen rearrangement reaction (CR) for the preparation of microporous polymers.…”
Section: Macromolecular Tr Chemistrymentioning
confidence: 99%
“…[3,3]-Sigmatropic rearrangement is another powerful and reliable pericyclic reaction, allowing for the stereoselective construction of C-C bond. 11 However, this rearrangement cannot be applied to polymerization other than the post-modification of side-chains [12][13][14][15][16] because it is an intramolecular reaction, which intrinsically forms and breaks the bond simultaneously (Scheme 1Ab).…”
Section: Introductionmentioning
confidence: 99%